HUBUNGAN DUKUNGAN SUAMI DAN PENGETAHUAN IBU HAMIL DALAM PEMERIKSAAN ANTENATAL CARE DI PUSKESMAS TANJUNG UNCANG - Yanti Domeska Hutabarat; Wan Intan Parisma (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
Antenatal Care is a health screening service provided to mothers during their pregnancy period in accordance with the standard of antenatal care, which includes several elements of service, blood pressure, measurement of Upper Arm Circles, measurement of height, immunization, giving Tablets, determining fetal heart rate, conducting speeches, laboratory test services, blood hemoglobin tests, examining urine protein, checking blood type The purpose of this study was to find out the relationship between husband's support and knowledge of pregnant women in prenatal care in Tanjung Uncang Community Health Center. The research design used in this study was a cross-sectional approach — this research conducted in Tanjung Uncang Health Center in 2018 with a sample of 31 people. Of the 31 respondents as many as 15 people (49%) respondents whose knowledge is excellent, as many as ten people (32%) whose knowledge is sufficiently supported and six people (19%) respondents lack knowledge. As many as 12 people (39%) respondents whose husband's support was excellent, ten people (32%) had enough support from their husbands, and nine people (29%) their husband's support was lacking. Then it can be stated that there is a relationship between husband's support and the knowledge of pregnant women in the Tanjung Uncang health center.